UPAYA MENINGKATKAN HASIL BELAJAR SISWA KELAS 4 PADA MATA PELAJARAN BAHASA INDONESIA MATERI TEKS PROSEDUR MELALUI PENDEKATAN TEACHING AT THE RIGHT LEVEL (TARL) DENGAN METODE MEMBACA BERIMBANG DI SDN TEGUHAN 02 - Angger Bagas Aryadinata; Moch Azra Alifvia Khoirur Ridwanudin; Ridwan Ardiansyah; Melik Budiarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the learning outcomes of fourth-grade students at SDN Teguhan 02 in the Indonesian Language subject, specifically in the procedural text material, through the implementation of the Teaching at the Right Level (TaRL) approach combined with the Balanced Reading method. The TaRL approach is employed to align instruction with the students' actual ability levels, while the Balanced Reading method is applied to gradually develop reading skills through shared reading, guided reading, group reading, and independent reading. This research is a Classroom Action Research (CAR) conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. Data were collected through observation, learning outcome tests, documentation, and interviews. The results of the study indicate a significant improvement in students’ learning outcomes. The average student score increased from 59 in the pre-cycle to 79 in the first cycle and reached 88.67 in the second cycle, with a mastery learning percentage of 100%. These findings suggest that a learning strategy based on students' actual competencies, supported by a comprehensive literacy approach, can effectively enhance students’ understanding of procedural texts. Moreover, this approach positively influences students' motivation and active participation during the learning process.